FLOOD PREVENTION BASED ON DISASTER RISK MANAGEMENT IN MALANG CITY - Putri, Galih WIjayanti Aspiyo; Ulum, Mochamad Chazienul (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
This research is based on the many incidents in Malang City related to flood disasters. Many of these incidents are caused by puddles or runoff of rainwater, which is not channeled properly through drainage channels due to the inability of drainage to accommodate the volume of rainwater and the lack of development of the RTH (Green Open Space). For this reason, the Malang City Government has made regulations regarding implementing disaster management in Malang City Local Regulation Number 1 of 2017. This research aims to describe and analyze the implementation of policies to prevent floods and waterlogging based on disaster risk management in Malang City. This research uses descriptive research with a qualitative approach. This research focuses on policy implementation to prevent floods and waterlogging based on disaster risk management in Malang City using the Edward III policy implementation model. Data sources are primary data sources and secondary data sources. Data collection techniques include interviews, observation, and documentation. Test the validity of the data using triangulation techniques. This research indicates that implementing flood and waterlogging disaster prevention policies has not been fully implemented properly. It has been implemented well when viewed from several aspects, such as communication, disposition, and bureaucratic structure. However, if seen from the aspect of resources, especially facility resources, they are still inadequate and not ideal for the two agencies involved. It can be concluded that this policy is still not successful, and there is a need for evaluation regarding this policy.